IMPROVING THE TECHNIQUE FOR CALCULATING THE PARAMETERS AND CONTROL OF A HYBRID PHOTOVOLTAIC SYSTEM WITH BATTERY FOR SELF-CONSUMPTION OF A LOCAL OBJECT - ШАВЬОЛКІН, О. О.; МАРЧЕНКО, Р. М. (Technologies and Engineering, 2024)
Purpose. Increasing the degree of energy use of a hybrid photovoltaic system with a battery for the local object’s own consumption, taking into account deviations in the load schedule relative to the calculated one and energy generation relative to the forecast value while reducing electricity consumption from the grid. Methodology. Analytical methods of calculation in electrical circuits and results of processing archival data of photovoltaic battery generation for a given point of location of the object using computer simulation to evaluate the results. Results. The technique for selecting parameters of a photovoltaic system based on archival generation data for 5 years has been improved, making it possible to increase the reliability of estimating the expected values of the degree of reduction in electricity consumption. Originality. The control principle with setting the active power based on the forecast of the generation of a photovoltaic battery according to the accepted load schedule with correction in the process of forming a graph of the battery charge level SoC(t) has been developed. This provides the possibility of compensating deviations of the load schedule from the estimated and generation of the photovoltaic battery with respect to the forecast value up to 20% while reducing the electricity consumption and increasing the degree of utilization of the energy of the photovoltaic battery. This is carried out at a given limit on the depth of battery discharge. Compliance of the actual SoC(t) schedule with the given one is achieved by adjusting the active power consumption from the grid according to the SoC deviation with a given time discreteness. A variant of forming the SoC(t) graph is proposed, which provides the possibility of correction during low generation of a photovoltaic battery with leveling the power consumption graph. Practical value. The obtained decision regarding the formation of the SoC(t) graph can be used in the design of photovoltaic systems for the self-consumption of local objects.